PENINGKATAN KEMAMPUAN MENULIS MAKALAH MAHASISWA PRODI PENDIDIKAN SEJARAH DALAM MATA KULIAH PENULISAN KARYA ILMIAH MELALUI PENDEKATAN DEEP DIALOGUE/ CRITICAL THINKING - Insan Fahmi Siregar (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2019)
Barriers are often found in teaching writing scientific papers in college, the most basic is to find, select, specify, and develop a writing topic. These constraints led students lack confidence and do not have the courage to write. Based on the symptoms expressed above, it is important to do the classroom action research in order to improve the process of learning to write papers in the subject of Writing Scientific Writing. One of the lessons that can be used as an alternative to achieve this goal is learning-based Deep Dialogue / Critical Thinking. Based on two cycles of action research found that there was a significant increase in the ability of students to write papers, both the evaluation of the test results and observations at the time of discussion. Students have been able to write papers correctly. The ability of students to write papers has improved in all aspects of the indicator.